T. Venclova 's Word l Text Conception in the Criticism of the l 970s - 1990s - Klimaitė-Keturakienė, Eglė (Respectus Philologicus, 2002)
Venclova's word / text sources were hidden in the synthesis of the West and the East poetical cultures, in the poetical experience of the Russian "silver age" (especially in O. Mandelstam's experience of critical thought) which formed an engagement to the language problems, the liberty of thinking and the sensation of distance. T. Venclova's critical method is more than the representation of J. M. Lotman's structural theory, it becomes the peculiar continuation of the creation between a critic and a text. T. Venclova's reflection of poetry is very important in order to understand his criteria of literature estimation. The conception of poetry embodies acmeism and structural poetical experience, M. Heidegger's language reflection, T. S. Eliot's principle of impersonality. Lithuanian literature and its process are reflected from a universal perspective in the context of the world literature. The critic also discovered and analyzed sovietism features: the deformed cultures, the low intellectual level, pseudopatriotism, the lack of tolerance. In Venclova's critical articles the idea of an opened human for himself and for the world, the importance of a dialogue among different cultures are propagated.
Keywords: Lithuanian literature; literary criticism; poetry; word; text; language; critical method; structuralism